Kekerasan Verbal Orang Tua Sebagai Prediktor Kepercayaan Diri Anak Usia Dini - Ottu, Maria; Amseke, Fredericksen Victoranto (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
Self-confidence is an individual's ability to understand and be confident in his own capacity, confident in achieving the expected goals, not anxious in acting, warm and polite in interactions and confident in his abilities. This study aims to determine the effect of parental verbal violence on self-confidence in children aged 4-6 years in Fenun Village, South Amanatun District. This research uses quantitative methods. Data collection tools used a scale of parental verbal violence and a scale of self-confidence for children aged 4-6 years. The respondents for this research were 75 parents of children in Fenun Village, South Amanatun District, South Central Timor Regency. The data analysis technique uses simple linear regression analysis. The results of this study prove that there is a negative and significant influence on the self-confidence of young children aged 4-6 years, amounting to 27.5%. The higher the verbal violence of parents, the lower the self-confidence of young children aged 4-6 years in Fenu Village, South Amanatun District, South Central Timor Regency. Keywords: parental verbal abuse; self confidence, early childhood